B(C6F5)3 promoted cyclisation of internal propargyl esters: structural characterisation of 1,3-dioxolium compounds - Hansmann, Max M.; Melen, Rebecca L.; Rominger, Frank; Hashmi, A. Stephen K.; Stephan, Douglas W. (Chemical communications, 2014)
The reactions of internal propargyl esters with B(C6F5)3 provide access to stable zwitterionic 1,3-dioxolium compounds which are characterised by X-ray diffraction. These 6π-electron systems show no significant aromatic stabilisation.